‘of evident invisibles’: Ethnography as intermediation - Pina-Cabral, Joao (2023)
Evident invisibles emerge in the ethnographic encounter which change the whence and the whither of the ethnographic gesture. Long ago, Margaret Mead critiqued anthropologists for ignoring ‘the world in between’ that makes their fieldwork possible – this article takes the argument a step further, proposing that all ethnographic encounters are fundamentally ‘amidst’. Thus, it calls for a shift from translation to intermediation as the guiding trope of ethnography. Although the practice of ethnography requires the objectification of a ‘field’, metaphysical pluralism remains the fundamental condition of ethnographic intermediation. In light of that, the article critiques (a) the practice of describing our main methodological disposition as ‘participant observation’, arguing instead for the older term ‘intensive ethnographic research’; and (b) the implicit use of the trope of ethnography-astranslation. Ethnographic examples are taken from the author’s own fieldwork in the coastal mangroves of southern Bahia (northeast Brazil) in the late 2000s.